TI_GERICHTE 11.2017.68 vom 8. Mai 2019 , Protezione della personalità: comunicazione di dati personali ad autorità estere - TI Tribunale d'appello (2019)
Protezione della personalità: comunicazione di dati personali ad autorità estere